(untitled) (Conference Zone, 2022)
Students with highly developed mental abilities are one of the guaranteed main assets of the university. One of the most important goals of the modern higher education system is to prepare competitive specialists who have a high level of professional training and are well-rounded as individuals, who are able to work without stopping on expanding their knowledge and skills throughout their lives. A student’s achievements in higher education play an important role in his/her becoming the best student. They make a great contribution to the country’s economic and social development by becoming the best leaders and competitive workforce for the country.